Penerapan Konsep Analisis Bauran Pemasaran dalam Strategi Meningkatkan Jumlah Mahasiswa (Studi Kasus: Manajemen Informatika STMIK Logika) - Ari Lestari (Syntax Idea)
Education is a form of conscious, tangible, and systematically planned activity aimed at creating a continuous learning atmosphere and process, actively developing self-potential to possess spiritual strength, self-management, intelligent personality, noble character, and both soft and hard skills needed by individuals, society, and the nation. The problem faced by the School of Information Management and Computer Logic is the failure to achieve the target number of student admissions for the year 2023 (a decrease in numbers). Therefore, without concrete action, it is feared to impact this Higher Education institution, especially the Information Management and Computer department. This study aims to formulate policies and alternative strategies based on the marketing mix model to increase public interest in choosing Logika Higher Education in the future. The independent variables studied are derived from the marketing mix strategy, namely Curriculum, Cost, Location, Promotion, Educational Staff and Personnel, Process, and Service. Meanwhile, the dependent variable is the Decision to Choose. The benefit obtained is an increase in the number of students enrolling in STMIK Logika, especially the Information Management and Computer Logic study program.